Selectivity in the Application of Rules of International Law and Its Impact on International Legitimacy “ An Analytical Study of Iranian Case” (Comprehensive Journal of Science, 2026)
This research examine the phenomenon of selectivity in the application of rules of international Law , considering it one of the most prominent challenges facing the structure of the contemporary international legal system. It aims to analyze the fundamental concept of this phenomenon and explore its manifestations in international practice , with a particular focus on the Iranian case as an applied model revealing the intersection between politics and Law .The study also addresses the role of international judiciary   particularly the international court of justice , in limiting such selectivity. The study concludes that selectivity undermines international legitimacy and threatens the principle of the rule of Law , which necessitate institutional and legal reforms at the international level.